Stability of nonextraction Class II malocclusion treatment with elastics - Niederberger, Ana Liesel Guggiari (2018)
The objective of this study was to evaluate the long-term stability after successful nonextraction Class II malocclusion treatment with elastics. A sample of 43 patients with Class II malocclusion was divided into two groups. The elastic group (EG) consisted of 20 patients who were treated with fixed appliances associated with Class II elastics. The headgear group (HG), consisted of 23 patients treated with fixed appliances and extraoral headgear. Pre-, post-treatment, and long-term post-treatment lateral radiographs and dental casts were evaluated. T-tests were used to compare the treatment changes and long-term post-treatment changes between the groups. The groups were matched regarding initial age, time of long-term post-treatment evaluation, initial malocclusion severity, quality of treatment result, and all pretreatment cephalometric variables. Patients of the EG presented greater treatment time, were older at the post-treatment and at the long-term post-treatment evaluation stages. During treatment both groups showed similar changes. Intergroup comparisons of long-term post-treatment changes showed slight mandibular retrusion in the EG and mandibular protrusion in the HG. The maxillary molar showed significant mesialization in the HG group. There were no intergroup significant occlusal differences during the long-term post-treatment period, with exception of the overjet, which maintained stable in the EG and showed improvement in the HG group. Nonextraction Class II malocclusion treatment with elastics or with extraoral headgear have similar long-term post-treatment stability.